Numerical modelling of water filtration - Toh, Zhi Yong (2019)
The project aims to develop a numerical modelling of a water filtration system. A mathematical formulation will be derived to solve a convection-diffusion problem. Finite volume method will be proposed to solve this problem to provide a numerical solutions. The method is studied in this project and the application of the method on the problem will be used to study the salt concentration in water filter with two semi-permeable membranes along the top and the bottom of the system. This method will then be solved using a MATLAB software problem, to present the solutions of the finite volume method in a one-dimensional steady-state pure diffusion problem.